Mô hình kinh tế vi mô với tiến bộ kĩ thuật công nghệ và vấn đề điều khiển tối ưu - Thập, Lê Huy (Journal of Computer Science and Cybernetics, 2016)
The model presented in this paper is microeconomic one in which both the nonnegative decay rates of pollutions and the rates of the ecological technical progresses are etudied. The optimal control theory and  the numerical method are applied to find the  optimal controller maximizing the integral of the utility function.